Do weight and BMI predict the results of surgical treatment with ESIN in pediatric tibial shaft fractures? - Martina Marsiolo; Angelo Gabriele Aulisa; Giulia Masci; Alessia Poggiaroni; Marco Giordano; Valeria Calogero; Francesco Falciglia (Journal of Orthopaedics and Traumatology)
Abstract Background Diaphyseal leg fractures are common in pediatric age, and the most used treatment is surgery using elastic stable intramedullary nailing (ESIN). In the past, a cutoff of 50 kg was the limit of weight indication for the use of ESIN. In literature, the concept of BMI has recently been introduced to evaluate the results owing to an increase in the incidence of obesity in children; up to now, it has only been used in one study for the femur but never in the tibia, although more than one author suggests doing so. The objective of this study was to research a correlation between weight, BMI, and the results of ESIN treatment. Materials and methods A total of 84 patients treated with ESIN from 2013 to 2021 were included; the inclusion criteria were clinical and radiographic data until complete healing and the presence of weight and height data collection; patients with an exposed fracture or neurovascular injury were excluded. The following were evaluated: clinical healing time in terms of load resumption (CHT), radiographic healing time (RHT), anteroposterior (APA) and lateral (LA) radiographic alignment, surgical time (CT), nonunion (NU), and delayed union (DC). Patients were divided into two weight groups (< 50; > 50). The statistical analysis was performed using STATA (Stata, College Station, TX, USA), and a p-value less than 0.05 was considered statistically significant. The Shapiro–Francia test was used to check the normality of each variable. Pearson’s correlation coefficient was calculated for the correlation between variables. Results A total of 84 patients with an average weight of 41.53 kg (18–85 kg) were included. Patients were divided into two groups; 62 patients weighing < 50 kg (GR1) and 22 patients weighing > 50 kg (GR2). We found a statistically significant correlation between weight and CHT, RHT, and ST and between BMI and CHT, RHT, and ST. Average results: GR1: CHT 55.84 days; RHT 48.79 days; ST 61.68 min and GR2: CHT 63.27 days; RHT 55.77 days, ST 79.32. We found no significant difference in CHT and RHT between the two groups, while a significant difference for ST was observed. Conclusions We confirm that ESIN nails can also be used in patients weighing > 50 kg affected by tibial shaft fractures; in fact, we found no statistical differences between the two groups’ clinical and radiographic healing times. Moreover, we found no difference in results between weight and BMI for tibial shaft fracture. The statistical difference correlation in ST between GR1 and GR2 does not imply an important difference in clinical practice.